Biological Monitoring of Heavy Metal Pollution [electronic resource] : Land and Air - Martin, M. H. author. (Dordrecht : Springer Netherlands, 1982)
In the past two decades there has been an increasing public awareness of the hazards that exist from the contamination of the environment by toxic substances. 'Heavy metals' and the terrestrial environment are but one facet of the impact of toxic substances on the natural environment, and the use of biological materials for indicating the occurrence of, and continually monitoring the presence of, these materials is a specific topic which is of considerable interest to a diverse range of individuals, organisations and disciplines. It was our intention when we first en visaged this book that it should contain a description of a range of circumstances in which biological monitoring techniques have been employed in the terrestrial environment and that it should be seen as a practical text which dealt with the merits, shortcomings and suitability of biological monitoring materials. Monitoring is, however, a manifold process. It serves not only to provide information on past and present concentrations of toxic materials in various components of the environ ment, but also to provide information on the processes of environmental release, transport, accumulation and toxicity. Indeed, this may be one of the greatest virtues of biological monitoring over other forms of monitor ing. According to the skill of the staff employed in the monitoring procedure, the information that is accrued can have a vastly different value.